Seattle's Women Teachers of the Interwar Years : Shapers of a Livable City - Pieroth, Doris Hinson (Book collections on Project MUSE., 2004)
"Pieroth interviewed as many of these women as she could find, and quotes from the interviews enhance here lively, well-written narrative. Using details drawn from local newspapers and school publications, she demonstrates that the influence of this cohort of women made modern Seattle the livable place that it remains today. Seattle's Women Teachers of the Interwar Years is a significant contribution to the history of Seattle and the region, to women's history, and to the history of education."--Jacket.